Correlation between Steatosis Degree and Hypertension Degree in Non-Alcoholic Fatty Liver Disease Patients in Indonesia - Akbar, Femmy Nurul; Bralianti, Putri Dwi; Akbar, Ridad Thaufiq; Hendarto, Hari (International Journal of Membrane Science and Technology, 2023)
Non-alcoholic fatty liver disease (NAFLD) has been recognized closely linked to cardiovascular diseases including hypertension. The connection between these conditions can be attributed to lipotoxicity, that induces systemic inflammation by activating the sympathetic nervous system (SNS) and triggers the release of angiotensin II within the renin-angiotensin-aldosterone system (RAAS). This study examined the correlation between degree of steatosis and degree of hypertension in NAFLD patients at Hajj Hospital Jakarta in 2019-2022. A cross-sectional approach was used to analyse the medical record data obtained through consecutive sampling. B-mode abdominal ultrasound examination assessed the degree of steatosis in NAFLD. Blood pressure grading was based on the 2020 International Society of Hypertension (ISH) Global Hypertension Practice Guidelines. The data were processed using Somers’d test to define the correlation between steatosis and hypertension.Of 53 NAFLD subjects, 56.6% were female, and mild steatosis was dominant (54.7%). The proportion of hypertension among NAFLD patients was 39.7%, with a higher prevalence of 61.9% among those aged 50 years or older. Majority of patients were grade I hypertension, whereas all subjects with grade II hypertension exhibited severe steatosis. There was correlation between the degree of hypertension and steatosis patients with NAFLD, with a p-value of 0.029 and a weak correlation coefficient (r= 0.251). This study found a correlation between steatosis and degree of hypertension. It was suggested females aged 50 years or older with grade II hypertension should be screened for fatty liver.